Kertarajasa Buddhist College Inter-religious Learning from the Perspective of Self-Study of Teaching Practice - Latifah Latifah; Hery Yanto The (Khazanah Theologia, 2021)
Using the self-study of teaching practice (S-STP), this research examines the process of inter-religious learning at Kertarajasa Buddhist College. The S-STP applied to this study is a potential alternative to answer many teaching challenges that were left out by other educational research approaches. Due to the Covid-19 Pandemic, the courses of inter-religious learning were offered online. These courses were designed and taught by the first author who is a non-Buddhist teacher-educator works in a Buddhist teaching institution. The courses were delivered using various online learning tools, assisted with scaffold learning, and included guest lectures. In the learning process, students were given opportunity to interact with the instructor and guest lectures. The guest lectures are liyan (the others) and subject-matter experts. The interactions mean to develop students’ awareness of other religious communities and the room for them to experience the religious moderation. This study reveals that the S-STP provides scientific method for the instructor to study own teaching practices. The S-STP as a research approach enables the course instructor to reflect on opportunities and challenges on teaching. The research approach also enables the instructor to self-assess the professional development as a teacher-educator. Moreover, feedback from the critical friend unveiled strengths and weaknesses of the teaching that were possible unseen by the instructor.